Kualitas Input Pencari Kerja Peserta Pelatihan Pada Balai Latihan Kerja Kota Palangka Raya - Lies Fahimah; Desy Selawaty (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2018)
This research aims to find out, describe and analyze the performance of Training Hall (BLK) in the city of Palangka Raya. The method used in this study is qualitative, research conducted liquid research descriptive where the Training Hall (BLK) of Palangka Raya City is chosen as the location of research. Data collection techniques used through interviews, observation, and documentation of the job seeker's Penjaringan process until the implementation of the training Hall ever. Based on the results of the research and performance discussion of Training Hall (BLK) in the city of Palangka Raya is still less maximum because of the lack of the infrastructure of coaches, equipment ever, the building is registered obsolete, the interest of people who are still lacking The vocational training Hall of Palangka Raya City, as well as the maintenance costs of the equipment ever so that the training hall is not maximal in its implementation. From the research, the advice that can be given is on the trust of local governments and the central government to provide cost assistance to the Trust Training center in the city Palangka Raya in order to be run optimally Where to give improvement of facilities and infrastructure and infrastructure of the trainer who is able to maximize the management of the training hall for the design and the results of quality human resources and produktive.